Guidelines for the diagnosis and management of cystathionine beta-synthase deficiency - Morris, Andrew A M; Kožich, Viktor; Santra, Saikat; Andria, Generoso; Ben-Omran, Tawfeg I M; Chakrapani, Anupam B; Crushell, Ellen; Henderson, Mick J; Hochuli, Michel; Huemer, Martina; Janssen, Miriam C H; Maillot, Francois; et al. (Journal of inherited metabolic disease, 2017)
Cystathionine beta-synthase (CBS) deficiency is a rare inherited disorder in the methionine catabolic pathway, in which the impaired synthesis of cystathionine leads to accumulation of homocysteine. Patients can present to many different specialists and diagnosis is often delayed. Severely affected patients usually present in childhood with ectopia lentis, learning difficulties and skeletal abnormalities. These patients generally require treatment with a low-methionine diet and/or betaine. In contrast, mildly affected patients are likely to present as adults with thromboembolism and to respond to treatment with pyridoxine. In this article, we present recommendations for the diagnosis and management of CBS deficiency, based on a systematic review of the literature. Unfortunately, the quality of the evidence is poor, as it often is for rare diseases. We strongly recommend measuring the plasma total homocysteine concentrations in any patient whose clinical features suggest the diagnosis. Our recommendations may help to standardise testing for pyridoxine responsiveness. Current evidence suggests that patients are unlikely to develop complications if the plasma total homocysteine concentration is maintained below 120 μmol/L. Nevertheless, we recommend keeping the concentration below 100 μmol/L because levels fluctuate and the complications associated with high levels are so serious.
Keywords: homocystinurie; cystathionin-beta-synthasa; Cystathionine beta-Synthase; homocystein; Homocystinuria; Pyridoxine; methionin; Methionine; Humans; pyridoxin; lidé; Betaine; Homocysteine; betain